2019
DOI: 10.1177/1321103x19843001
|View full text |Cite
|
Sign up to set email alerts
|

Socially inclusive practices in the music classroom: The impact of music education used as a vehicle to engage refugee background students

Abstract: As schools become increasingly culturally diverse, globalisation and cross-cultural exchange challenge teachers in complex but exciting ways. This article reports on the impact of music education for students in a secondary school in Victoria, Australia. Socially inclusive practices were a focus of the study as the school has a high percentage of young people with a refugee background. A number of school-based musical experiences provided opportunities for cross-cultural exchange and negotiation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
1
20
0
4
Order By: Relevance
“…The key distinguishing feature of transculturation is the emphasis on cultures’ reciprocal flows and the transformative effects it has on constructions and understandings of self and others. It has been used to ‘describe and analyse the complex, reciprocal, bi- or multi-directional flows and exchanges between cultures that share geographical, social, economic, linguistic or other kinds of proximity’ (Crawford, 2019a, p. 3). Pratt (1991) referenced transculturation to examine ways in which people negotiate intercultural spaces or ‘contact zones’ within the arts context.…”
Section: Acculturation Integration and Transculturationmentioning
confidence: 99%
See 4 more Smart Citations
“…The key distinguishing feature of transculturation is the emphasis on cultures’ reciprocal flows and the transformative effects it has on constructions and understandings of self and others. It has been used to ‘describe and analyse the complex, reciprocal, bi- or multi-directional flows and exchanges between cultures that share geographical, social, economic, linguistic or other kinds of proximity’ (Crawford, 2019a, p. 3). Pratt (1991) referenced transculturation to examine ways in which people negotiate intercultural spaces or ‘contact zones’ within the arts context.…”
Section: Acculturation Integration and Transculturationmentioning
confidence: 99%
“…Transculturation involves the mutual transformative effects of ‘giving and taking’ across cultures for both refugee migrants and the community of destination. Studies have indicated that students were able to translate aspects of self into a new context using the arts learning they gained from participating in music classes (Crawford, 2017, 2019a); which is part of the ongoing dynamic of identity construction and of settlement experiences (Hale & de Abreu, 2010; Zittoun et al., 2003).…”
Section: Acculturation Integration and Transculturationmentioning
confidence: 99%
See 3 more Smart Citations